RREPRESENTASI PERAN ORANG TUA TUNGGAL PADA PEMBENTUKAN KARAKTER ANAK DENGAN SINDROM ASPERGER DALAM DRAMA KOREA MOVE TO HEAVEN (ANALISIS SEMIOTIKA JOHN FISKE) - Diandra Pratisthita Indraswar, Ni Luh Ayu; Lukmantoro, Triyono; Dwiningtyas Sulistyani, Hapsari (Interaksi Online, 2024)
Single parents certainly experience difficulties in filling multiple roles, but being a single parent with a child with special needs presents challenges and complexities on a different level. Media has a role as a source of information as well as entertainment, to accurately display a social issue in society, so that individuals, groups or a culture are represented. This research describes the role of men as single parents in shaping the character of children with Asperger's syndrome in the Korean drama Move to Heaven by implementing John Fiske's semiotic theory through the level of reality, the level of representation and the level of ideology. The role of men as single parents in forming the character of children with Asperger syndrome shows inconsistencies in the discipline aspect. Then, in the affection aspect, the dominant role of men as single parents is shown, which ignores children's autonomy. Then, in the aspect of self-development, men as single parents show that children who understand their self-concept still need validation from other people. Finally, in the social aspect, it is not shown in depth the instillation of social values by men as single parents with children with Asperger's syndrome. The Korean drama Move to Heaven tends to romanticize the role of men as single parents with children with Asperger's syndrome by presenting dramatic elements that support the conception of hegemonie masculinity in society